Floc growth during flocculation - Lin, Chin-chi; Vigneswaran, S.; Chongrak Polprasert; Nguyen, Cong Thanh; Carl Duisberg Gasellschaft, Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1982)
Flocculation is used to promote settling efficiency, by mixing, aggre- gation of colloidal particles into readily settleable floes. The floc size at different solid concentration, flocculation time, mean velocity gradient, pH value, dose, and polyelectrolyte concentration was studied for artificial clay-water suspension using jar test. The floc size was measured using mi- croscope, the most appropriate method although it is laborious. The experiments revealed that pH value, G value, flocculation time, flocculant dose, and polyelectrolyte concentration have significant influence on floc growth and ultimate size of floc, whereas solid concentration does not have significant influence on the ultimate floc size but on the density of floes. Therefore solid concentration is also an important parameter on the efficiency of removal of colloidal particles. The modified Boadway's (1978) and Tambo's (1978) equations for ultimate floc size and floc growth rate respectively were successful to explain the flocculation behavior.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng) - Asian Institute of Technology, 1982
Keywords: Tanning -- Waste disposal